Patient’s Perception and Satisfaction with Healthcare Professionals at Primary Health Care Facilities in Onelga (Ogba Egbema Ndoni LGA) - Orukwowu, Udo; Oji, Aleruchi Lenchi; Kue, Jane Baridah (Chakra Brahmanda Lentera Institute, 2024)
Background: This study investigates the patient's perspective and contentment with healthcare professionals at primary health care facilities in Onelga (Ogba Egbema Ndoni LGA). Employing a survey research design, data was collected from 100 healthcare professionals using a structured questionnaire. The study's objectives include assessing patient satisfaction with healthcare services, exploring the correlation between physician behavior and healthcare services, and determining factors influencing satisfaction levels in the study area. Methods: Demographic data analysis reveals the majority of respondents are male, aged above 60, with educational backgrounds ranging from FSLC to MSC/PGD/PHD. Results: Patient satisfaction findings indicate a significant proportion agreeing or strongly agreeing with positive sentiments regarding healthcare services, physician behavior, and facility cleanliness. Additionally, statistical tests affirm a significant relationship between healthcare services and patient satisfaction. The study concludes that patient satisfaction is influenced by efficient service delivery, physician behavior, and facility infrastructure. Conclusion: Recommendations include regular assessment of patient satisfaction, enhancing healthcare service efficiency, and addressing factors influencing patient contentment. This research contributes to the broader understanding of patient perspectives in healthcare settings, facilitating improvements in service quality and overall patient experience